Ureter mixed neuroendocrine-non-neuroendocrine neoplasm: a case report and literature review - Zhou, Bing; Gan, Xing; Li, Xiaohua; Peng, Lizi; Hao, Hua (Frontiers in Oncology, 2024)
Cases of mixed neuroendocrine-non-neuroendocrine neoplasms (MiNENs) of the urinary system are rare, and reports of primary MiNENs in the ureter are lacking. Herein, we present the case of a 71-year-old man who presented with painless gross hematuria and weight loss. Contrast-enhanced abdominal computed tomography (CT) revealed a tumor, comprising small cell neuroendocrine carcinoma (SCNEC) and adenocarcinomatous components, attached to the ureter. The SCNEC components were strongly positive for synaptophysin, CD56 and INSM1 and adenocarcinomatous components were strongly positive for CDX2 and cytokeratin 20, respectively. Four weeks post-surgery, the patient received four cycles of cisplatin-based chemotherapy; the 7-month follow-up CT confirmed that he was healthy without disease recurrence. The occurrence of MiNEN in the ureter with SCNEC and adenocarcinomatous components is extremely rare, wherein histopathological and immunohistochemical features aid in the diagnosis MiNEN. With its aggressive nature, MiNEN can only be effectively treated by early diagnosis and radical surgery.